Profil pelancong sukan di Tasik Kenyir dan implikasi ke atas strategi pemecahan pasaran dan pemilihan destinasi pelancongan - Abdul Rahman, Nora (2006)
270 foreigners and 129 locals from a total number of 399 tourists of Tasik Kenyir were chosen as samples of this research. They were issued a set of questionairre divided into four sections. Section A consists of 18 items related to the respondents’ demographical informations (age, sexs, marital status, race, religion, education background, profession, monthly imcome, and purpose of visiting. Section B is an Instrument Measuring Leisure Motivation, consisting of 48 items extracted from the Theory of Leisure Motivation by Reghab and Beard (1983). This section measures the roles, characteristics, psychographical and social factors which provides information related to motives of engaging leisure activities. Section C consists of 14 items related to sports tourism, active and passive. Section D consists of semantic differential scale by Attle and Yiannakis, aimed to determine tourist destination attributes. The outcome of this research shows that 163 of 399 tourists were active sports tourist and also 163 were passive sports tourist. It was also found that there is a corelation between the presence of tourists in Tasik Kenyir and the demographic factors, psycography, pull and push factors. They were in Tasik Kenyir to visit and to appreciate the beauty of Tasik Kenyir. This conclusion is based on the findings that show a number of 85 (52 %) sports active tourists and 91(55.8 %) sport passive tourists went to Tasik Kenyir for sports. A total number of 76 (46.6%) sports active tourists (46.6 %) and 75 (46.0 %) sport passive tourists were both participants and tourists at Tasik Kenyir for internal satisfaction to release from stress, mental relaxation, escapism from problems and for physical fitness.